Rheological model of the lithosphere along profile VII in the Eastern Carpathians - DÉREROVÁ, Jana; BIELIK, Miroslav; GODOVÁ, Dominika; MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2021)
We used 2D integrated geophysical modelling approach to calculate the temperature distribution in the lithosphere along profile VII passing through the Eastern Carpathians. With assigned rheological parameters of rocks and obtained temperature field, we derived the rheological model of the lithosphere along the studied profile. We have calculated the strength distribution in the lithosphere, based on the brittle and ductile deformation, for compressional and extensional regimes and the vertically integrated strength along the profile. To illustrate the strength distribution in different tectonic units, we have calculated the yield strength envelopes for chosen lithospheric columns. Ours results show that the dominant regime is compressional and the largest strength occurs on the boundary between the upper and lower crust. Along the studied profile, the strength decreases from its high values in the European platform towards its minimum in the Trans-European Suture Zone (TESZ). In the Eastern Carpathians, the strength increases, reaches two maxima, the first in the Outer Eastern Carpathians, and the second in the Inner Eastern Carpathians, where the highest values of strength can be observed. Another local maximum along the profile can be observed in the Apuseni Mountains, while the minimal strength is observed in the Transylvanian Basin. The diverse rheological behaviour of studied tectonic units seems to be in accordance with their lithospheric structure and tectonics.